Unconventional Strategic Management and Intelligence Operations: A Nexus of Adaptability and Information Dominance - Kanellopoulos, Anastasios-Nikolaos (HAPSc Policy Briefs Series, 2024)
This paper examines the convergence of unconventional strategic management and intelligence operations as a critical paradigm shift for modern intelligence agencies. Utilizing a literature review methodology, the study explores the core components of unconventional strategic management—strategic agility, innovation, ecosystem thinking, scenario planning, and ambidexterity—and their potential application within the intelligence context. The research concludes that integrating unconventional management principles into intelligence operations is essential for navigating complex and dynamic security environments, fostering innovation, and achieving information dominance. This integration enhances organizational adaptability, resilience, and effectiveness, positioning intelligence agencies to better anticipate and respond to emerging threats.